EKSPLORASI TIMBRE VIBRAPHONE MELALUI TEKNIK BOW PADA KOMPOSISI GEMA SWARA KARYA JUAN ARIEF - Firstian Qq Ananda; Juanita Vannesa Livia Asnawi (TAMUMATRA, 2026)
This study aims to analyze the exploration of timbre on the vibraphone instrument through the use of bow techniques in the composition Gema Swara by Juan Arief. The background of this study encourages the exploration of timbre through bow techniques on the vibraphone. The method used is a qualitative approach with a musical analysis that focuses on playing techniques, sound character, and composition structure. Data collection was carried out through literature studies, observation of performance recordings, and analysis of the work's scores. The results show that the bow technique is able to produce a soft, long-resonating, and atmospheric timbre, thus playing an important role in forming musical texture and atmosphere. The interaction between the bow and mallet techniques creates a timbre contrast that enriches the dynamics. In addition, the use of improvisation with the slendro scale shows an integration between traditional and western musical elements. In conclusion, the exploration of timbre through bow techniques not only expands the possibilities of musical expression on the vibraphone. Keyword: Eksploration, Vibraphone, Bow Technic.